Product Overview of Physics Student Enterpreneurship in Educational Enterpreneurship Courses - Juita, Dewi; M, Yusmaridi; Sunarti, Vevi (KOLOKIUM Jurnal Pendidikan Luar Sekolah, 2023)
The educational entrepreneurship course is a subject that is in accordance with the vision of the UIN Imam Bonjol Padang campus, namely to form graduates who are creative and independent. This course is given to students majoring in physics education which is a science group. This research aims to find out to what extent students with science knowledge are able to provide creative ideas for entrepreneurial products that they can design. This research uses a qualitative approach with descriptive methods. The instrument in this study was an unstructured interview questionnaire and documentation in the form of a draft proposal submitted by students. From the research results, it was found that 70% of students wanted to build their business in a field according to their knowledge, namely physics education, while 30% of students chose to build their business outside their scientific field. Furthermore, in the scientific field of business that physics education students are interested in is building face-to-face physics learning courses, building online learning courses using a special platform or through their own YouTube channel, and there are also those who choose to be creators of physics learning media which will be used by teachers. physics in school learning. for outside the scientific field, students are interested in the business of selling viral food and drinks, importing clothes traders, becoming typists, building repair shops, and becoming side dishes traders in the campus environment.